First trimester ultrasound tests alone or in combination with first trimester serum tests for Down's syndrome screening - Alldred, S Kate; Takwoingi, Yemisi; Guo, Boliang; Pennant, Mary; Deeks, Jonathan J; Neilson, James P; Alfirevic, Zarko (Cochrane database of systematic reviews, 2017)
Down's syndrome occurs when a person has three, rather than two copies of chromosome 21; or the specific area of chromosome 21 implicated in causing Down's syndrome. It is the commonest congenital cause of mental disability and also leads to numerous metabolic and structural problems. It can be life-threatening, or lead to considerable ill health, although some individuals have only mild problems and can lead relatively normal lives. Having a baby with Down's syndrome is likely to have a significant impact on family life.Non-invasive screening based on biochemical analysis of maternal serum or urine, or fetal ultrasound measurements, allows estimates of the risk of a pregnancy being affected and provides information to guide decisions about definitive testing.Before agreeing to screening tests, parents need to be fully informed about the risks, benefits and possible consequences of such a test. This includes subsequent choices for further tests they may face, and the implications of both false positive and false negative screening tests (i.e. invasive diagnostic testing, and the possibility that a miscarried fetus may be chromosomally normal). The decisions that may be faced by expectant parents inevitably engender a high level of anxiety at all stages of the screening process, and the outcomes of screening can be associated with considerable physical and psychological morbidity. No screening test can predict the severity of problems a person with Down's syndrome will have. To estimate and compare the accuracy of first trimester ultrasound markers alone, and in combination with first trimester serum tests for the detection of Down's syndrome. We carried out extensive literature searches including MEDLINE (1980 to 25 August 2011), Embase (1980 to 25 August 2011), BIOSIS via EDINA (1985 to 25 August 2011), CINAHL via OVID (1982 to 25 August 2011), and The Database of Abstracts of Reviews of Effects (the Cochrane Library 2011, Issue 7). We checked reference lists and published review articles for additional potentially relevant studies. Studies evaluating tests of first trimester ultrasound screening, alone or in combination with first trimester serum tests (up to 14 weeks' gestation) for Down's syndrome, compared with a reference standard, either chromosomal verification or macroscopic postnatal inspection. Data were extracted as test positive/test negative results for Down's and non-Down's pregnancies allowing estimation of detection rates (sensitivity) and false positive rates (1-specificity). We performed quality assessment according to QUADAS criteria. We used hierarchical summary ROC meta-analytical methods to analyse test performance and compare test accuracy. Analysis of studies allowing direct comparison between tests was undertaken. We investigated the impact of maternal age on test performance in subgroup analyses. We included 126 studies (152 publications) involving 1,604,040 fetuses (including 8454 Down's syndrome cases). Studies were generally good quality, although differential verification was common with invasive testing of only high-risk pregnancies. Sixty test combinations were evaluated formed from combinations of 11 different ultrasound markers (nuchal translucency (NT), nasal bone, ductus venosus Doppler, maxillary bone length, fetal heart rate, aberrant right subclavian artery, frontomaxillary facial angle, presence of mitral gap, tricuspid regurgitation, tricuspid blood flow and iliac angle 90 degrees); 12 serum tests (inhibin A, alpha-fetoprotein (AFP), free beta human chorionic gonadotrophin (ßhCG), total hCG, pregnancy-associated plasma protein A (PAPP-A), unconjugated oestriol (uE3), disintegrin and metalloprotease 12 (ADAM 12), placental growth factor (PlGF), placental growth hormone (PGH), invasive trophoblast antigen (ITA) (synonymous with hyperglycosylated hCG), growth hormone binding protein (GHBP) and placental protein 13 (PP13)); and maternal age. The most frequently evaluated serum markers in combination with ultrasound markers were PAPP-A and free ßhCG.Comparisons of the 10 most frequently evaluated test strategies showed that a combined NT, PAPP-A, free ßhCG and maternal age test strategy significantly outperformed ultrasound markers alone (with or without maternal age) except nasal bone, detecting about nine out of every 10 Down's syndrome pregnancies at a 5% false positive rate (FPR). In both direct and indirect comparisons, the combined NT, PAPP-A, free ßhCG and maternal age test strategy showed superior diagnostic accuracy to an NT and maternal age test strategy (P < 0.0001). Based on the indirect comparison of all available studies for the two tests, the sensitivity (95% confidence interval) estimated at a 5% FPR for the combined NT, PAPP-A, free ßhCG and maternal age test strategy (69 studies; 1,173,853 fetuses including 6010 with Down's syndrome) was 87% (86 to 89) and for the NT and maternal age test strategy (50 studies; 530,874 fetuses including 2701 Down's syndrome pregnancies) was 71% (66 to 75). Combinations of NT with other ultrasound markers, PAPP-A and free ßhCG were evaluated in one or two studies and showed sensitivities of more than 90% and specificities of more than 95%.High-risk populations (defined before screening was done, mainly due to advanced maternal age of 35 years or more, or previous pregnancies affected with Down's syndrome) showed lower detection rates compared to routine screening populations at a 5% FPR. Women who miscarried in the over 35 group were more likely to have been offered an invasive test to verify a negative screening results, whereas those under 35 were usually not offered invasive testing for a negative screening result. Pregnancy loss in women under 35 therefore leads to under-ascertainment of screening results, potentially missing a proportion of affected pregnancies and affecting test sensitivity. Conversely, for the NT, PAPP-A, free ßhCG and maternal age test strategy, detection rates and false positive rates increased with maternal age in the five studies that provided data separately for the subset of women aged 35 years or more. Test strategies that combine ultrasound markers with serum markers, especially PAPP-A and free ßhCG, and maternal age were significantly better than those involving only ultrasound markers (with or without maternal age) except nasal bone. They detect about nine out of 10 Down's affected pregnancies for a fixed 5% FPR. Although the absence of nasal bone appeared to have a high diagnostic accuracy, only five out of 10 affected Down's pregnancies were detected at a 1% FPR.